Political Strategies in Pre-Columbian Mesoamerica - Kurnick, Sarah (University Press of Colorado, 2016)
New data from a variety of well-known scholars in Mesoamerican archaeology reveal the creation, perpetuation, and contestation of politically authoritative relationships between rulers and subjects and between nobles and commoners. The contributions span the geographic breadth and temporal extent of pre-Columbian Mesoamerica-from Preclassic Oaxaca to the Classic Petén region of Guatemala to the Postclassic Michoacán-and the contributors weave together archaeological, epigraphic, and ethnohistoric data. Grappling with the questions of how those exercising authority convince others to follow and why individuals often choose to recognize and comply with authority, Political Strategies in Pre-Columbian Mesoamerica discusses why the study of political authority is both timely and significant, reviews how scholars have historically understood the operation of political authority, and proposes a new analytical framework to understand how rulers rule.